Áreas agroecológicas - Oliva, Gabriel Esteban; Behr, Santiago Javier; González, Liliana; Peri, Pablo Luis; Massara Paletto, Virginia; Rial, Pablo Eduardo; Livraghi, Enrique (Ediciones INTA, 2021)
Capítulo de libro.